Early-childhood temperament moderates the prospective associations of coping with adolescent internalizing and externalizing symptoms - Smith, Michele R.; Parrish, Krystal H.; Shimomaeda, Lisa; Zalewski, Maureen; Rosen, Maya L.; Rodman, Alexandra; Kasparek, Steven; Mayes, Makeda; Meltzoff, Andrew N.; McLaughlin, Katie A.; Lengua, Liliana J. (Frontiers in Psychology, 2022)
While appraisal and coping are known to impact adolescent psychopathology, more vulnerable or resilient responses to stress may depend on individual temperament. This study examined early life temperament as a moderator of the prospective relations of pre-adolescent appraisal and coping with adolescent psychopathology. The sample included 226 (62% female, 14–15 years) adolescents with assessments starting at 3 years of age. Adolescents were predominately White (12% Black 9% Asian, 11% Latinx, 4% Multiracial, and 65% White). Observed early-childhood temperament (fear, frustration, executive control, and delay ability) were tested as moderators of pre-adolescent coping (active and avoidant) and appraisal (threat, positive) on internalizing and externalizing symptoms during the pandemic. Interaction effects were tested using regression in R. Sex and family context of stress were covariates. Early-childhood temperament was correlated with pre-adolescent symptoms, however, pre-adolescent appraisal and coping but not temperament predicted adolescent psychopathology. Frustration moderated the relations of active and avoidant coping and positive appraisal to symptoms such that coping and appraisal related to lower symptoms only for those low in frustration. Executive control moderated the associations of avoidant coping with symptoms such that avoidance reduced the likelihood of symptoms for youth low in executive control. Findings underscore the role of emotionality and self-regulation in youth adjustment, with the impact of coping differing with temperament. These findings suggest that equipping youth with a flexible assortment of coping skills may serve to reduce negative mental health outcomes.